Characteristics of Short‐stay Critical Care Admissions From Emergency Departments in Maryland. (8th May 2017) - Chidi, Obiora O.; Perman, Sarah M.; Ginde, Adit A.
Abstract: Objectives: Critical care is an expensive and limited resource, and short‐stay critical care admissions may be treated in alternate, less costly settings. This study objective was to determine the proportion of critical care admissions with a short critical care length of stay (LOS) and identify the clinical characteristics and diagnoses associated with high and low rates of short‐stay critical care admissions. Methods: This study was a secondary analysis of the 2011 Maryland State Inpatient Database. The study included adult emergency department (ED) visits admitted to a critical care unit. We compared clinical data and discharge diagnoses for short‐ (≤1 day) versus longer‐ (≥2 days) stay critical care admissions. Results: A total of 30, 212 critical care admissions were eligible, of which 11, 494 (38.0%) were short stay. There were significant differences in age, insurance, and comorbidities between the short‐stay and the longer‐stay critical care admissions. Of short‐stay critical care admissions, 3, 404 (29.6%) also had a 1‐day overall hospital LOS. The diagnoses with the highest proportion of short‐stay critical care admissions were nonspecific chest pain (87.9%), syncope (70.6%), and transient cerebral ischemia (67.6%) and the lowest proportion were respiratory failure (17.9%), sepsis (19.4%), and aspiration pneumonitis (19.8%). Conclusions: Over one‐third of critical care admissions were short stay. Alternate strategies to manage these patients, including ED‐based critical care units or other venues of inpatient care, may be more cost‐efficient for selected patients.